Simulation of Human Gait and Lifting Motion - (NIM 13103101), RAJIV
Men perform many feats of movement to fulfill its daily activities. Walking, running, crawling, lifting objects, and ascending stairs are some of many basic movements that are commonly done. Every human movement is very complex; one activity may consist of many motions altogether. Take for example, walking, if it is viewed thoroughly, then each joint in the legs may move in numerous directions, therefore it will be very difficult to evaluate. To simplify the analysis, the human body is modeled as a multiple body system. A multiple body system is a group of links that is connected one to another. Then, from kinematic and dynamic analysis, the motions and forces that occur can be identified. Every human joint has its maximum strength to receive moments. With the limitation of the joint's strength, the capability to do motion is also limited. If in one motion a joint is exposed to excess moments, it will be injured. This research evaluates the human movement of walking and lifting objects with various conditions in the sagital plane. The walking movement is assessed in three conditions: normal step, stride, and quick step. Analysis of the kinematics and dynamics of the model is evaluated with multiple body dynamics with the aide of MATLAB software. Result consists of the force on the supporting ankle and moments in every joint. From the three walking conditions, the highest value is obtained in the quick step condition. The values confirmed are analogous with the results by Amirouche et al., 1990. Object lifting movement is analyzed for three different initial conditions with three variations of loading. From the moment analysis on each joint, the third initial condition is more likely to be susceptible to injury.